Demarginalizing the intersection of race and sex: A black feminist critique of antidiscrimination doctrine, feminist theory and antiracist politics - Crenshaw, Kimberle (The University of Chicago Legal Forum, 1989)
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; droit; féminismes noirs; incontournable; intersectionnalité; militance; pol4212; premier cycle; projet charge mentale; racisme; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

White privilege and male privilege: A personal account of coming to see correspondences through work in women's studies - McIntosh, Peggy (Wellesley College, Center for Research on Women, 1988)
Through work to bring materials and perspectives from Women's Studies into the rest of the curriculum, I have often noticed men's unwillingness to grant that they are overprivileged in the curriculum, even though they may grant that women are disadvantaged. Denials that amount to taboos surround the subject of advantages that men gain from women's disadvantages. These denials protect male privilege from being fully recognized, acknowledged, lessened, or ended.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discours dominant; intersectionnalité; privilèges; périodes historiques; racisme; ressource en ligne; régions géographiques; savoir expérientiel; sexisme; systèmes d'oppressions; états-unis

Learning from the outsider within: The sociological significance of black feminist thought - Hill Collins, Patricia (Social Problems, 1986)
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; intersectionnalité; point de vue situé; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; épistémologie; états-unis

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Black women: Shaping feminist theory - hooks, bell (Feminist theory: From margin to center, 1984)
Keywords: 1900-1999; EDI; amériques; approches et analyses; cours; fem1000; intersectionnalité; justice sociale; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis